[18F]-HX4 PET/CT hypoxia in patients with squamous cell carcinoma of the head and neck treated with chemoradiotherapy: Prognostic results from two prospective trials. (July 2020) - Sanduleanu, Sebastian; Hamming-Vrieze, Olga; Wesseling, Frederik W.R.; Even, Aniek J.G.; Hoebers, Frank J.; Hoeben, Ann; Vogel, Wouter V.; Tesselaar, Margot E.T.; Parvin, Daniel; Bartelink, Harry; Lambin, Philippe
Highlights: Early changes in hypoxia could be a promising biomarker to identify patients with unfavorable prognosis. Large differences were found between baseline and week 2 hypoxia PET signal. Neither baseline nor week 2 static parameters were associated with worse OS and local PFS. Abstract: Introduction: The presence of hypoxia in head-and-neck squamous cell carcinoma is a negative prognostic factor. PET imaging with [18F] HX4 can be used to visualize hypoxia, but it is currently unknown how this correlates with prognosis. We investigated the prognostic value of [18F] HX4 PET imaging in patients treated with definitive radio(chemo)therapy (RTx). Materials and methods: We analyzed 34 patients included in two prospective clinical trials (NCT01347281, NCT01504815). Static [18F] HX4 PET-CT images were collected, both pre-treatment (median 4 days before start RTx, range 1–16), as well as during RTx (median 13 days after start RTx, range 3–17 days). Static uptake at both time points (n = 33 pretreatment, n = 28 during RTx) and measured changes in hypoxic fraction (HF) and hypoxic volume (HV) (n = 27 with 2 time points) were analyzed. Univariate cox analyses were done for local progression free survival (PFS) and overall survival (OS) at both timepoints. Change in uptake was analyzed by comparing outcome with Kaplan-Meier curves and log-rank test between patients with increased and decreased/stable hypoxia, similarly between patients with and without residual hypoxia (rHV = ratio week 2/baseline HV with cutoff 0.2). Voxelwise Spearman correlation coefficients were calculated between normalized [18F] HX4 PET uptake at baseline and week 2. Results: Analyses of static images showed no prognostic value for [18F] HX4 uptake. Analysis of dynamic changes showed that both OS and local PFS were significantly shorter (log-rank P < 0.05) in patients with an increase in HV during RTx and OS was significantly shorter in patients with rHV, with no correlation to HPV-status. The voxel-based correlation to evaluate spatial distribution yielded a median Spearman correlation coefficient of 0.45 (range 0.11–0.65). Conclusion: The change of [18F] HX4 uptake measured on [18F] HX4 PET early during treatment can be considered for implementation in predictive models. With these models patients with a worse prognosis can be selected for treatment intensification.